Tamoxifen Inhibits CDK5 Kinase Activity by Interacting with p35/p25 and Modulates the Pattern of Tau Phosphorylation. Issue 4 (23rd April 2015) - Corbel, Caroline; Zhang, Bing; Le Parc, Annabelle; Baratte, Blandine; Colas, Pierre; Couturier, Cyril; Kosik, Kenneth S.; Landrieu, Isabelle; Le Tilly, Véronique; Bach, Stéphane
Summary: Cyclin-dependent kinase 5 (CDK5) is a multifunctional enzyme that plays numerous roles, notably in brain development. CDK5 is activated through its association with the activators, p35 and p39, rather than by cyclins. Proteolytic procession of the N-terminal part of its activators has been linked to Alzheimer's disease and various other neuropathies. The interaction with the proteolytic product p25 prolongs CDK5 activation and modifies the substrate specificity. In order to discover small-molecule inhibitors of the interaction between CDK5 and p25, we have used a bioluminescence resonance energy transfer (BRET)-based screening assay. Among the 1, 760 compounds screened, the generic drug tamoxifen has been identified. The inhibition of the CDK5 activity by tamoxifen was notably validated by monitoring the phosphorylation state of tau protein. The study of the molecular mechanism of inhibition indicates that tamoxifen interacts with p25 to block the CDK5/p25 interaction and pave the way for new treatments of tauopathies. Graphical Abstract: Highlights: The CDK5/p25 interaction is related to neurodegenerative diseases Tamoxifen, an antitumor agent, inhibits CDK5/p25 activity Tamoxifen acts by binding on p25 Tamoxifen can be used for further development of therapeutic drugs Abstract : Corbel et al. describe the discovery of a new target for the widely used drug tamoxifen: the CDK5/p25 interaction. Treatment of primary neurons with tamoxifen results in decreased phosphorylated forms of tau, one of the neuropathological hallmarks of Alzheimer's disease.